Perovskite solar cell based on interfacial chemical reaction and preparation method thereof
Patent Information
- Application Number
- CN202310942738.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-07-28
AI Technical Summary
[0004]本发明的目的是提供一种基于界面化学反应的钙钛矿太阳能电池及其制备方法,解决了现有技术中修饰分子影响界面传输和太阳能稳定性等问题
[0061] This invention provides an interface-modifying molecule as a raw material for a perovskite modification layer. The interface-modifying molecule reacts chemically with A-site ions in the light-absorbing layer of a perovskite solar cell, utilizing the strong reactivity of isocyanate groups and amine groups, to undergo the following reaction:
Smart Images

Figure CN116981272B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solar cell technology, and in particular to a perovskite solar cell based on interfacial chemical reactions and its preparation method. Background Technology
[0002] Since their introduction in 2009, perovskite solar cells have experienced rapid development over the past decade due to their high efficiency, low cost, and ease of fabrication. As a third-generation solar cell, perovskite solar cells have attracted widespread attention from many countries. However, due to the coating and high-temperature annealing processes involved in the fabrication of perovskite solar cells, numerous defects can exist at the interface formed between the perovskite light-absorbing layer and the charge transport layer during crystallization. The formation of these defects reduces the electrochemical performance of perovskite solar cells, leading to decreased device efficiency and stability.
[0003] Current solutions to this defect typically involve interface modification, with modifying molecules usually passivating defects in perovskite solar cells through coordination interactions. However, existing interface modifications based on coordination interactions suffer from problems such as weak coordination interactions and the influence of modifying molecules on interfacial transport and solar energy stability. Summary of the Invention
[0004] The purpose of this invention is to provide a perovskite solar cell based on interfacial chemical reactions and its preparation method, which solves the problems of the influence of modified molecules on interfacial transport and solar energy stability in the prior art.
[0005] To achieve the above objectives, the present invention provides a perovskite solar cell based on interfacial chemical reaction, comprising a conductive glass substrate, an electron transport layer, a perovskite light-absorbing layer, a perovskite modification layer, a hole transport layer, and a metal electrode stacked thereon.
[0006] The structural formula of the interface modification molecules used in the perovskite modification layer is:
[0007]
[0008] Wherein, core is a core group with large conjugation, and dendron is a dendritic group with isocyanate substituents.
[0009] Preferably, the core is
[0010]
[0011] One of them;
[0012] R1 and R2 are one of straight-chain alkyl, branched-chain alkyl, methoxy, and vinyl groups.
[0013] Preferably, dendron is One of them; wherein R3 is an isocyanate group, and R4 is one of a straight-chain alkyl group, a branched alkyl group, or a methoxy group.
[0014] Preferably, the interface-modifying molecules include, but are not limited to, the following structures:
[0015] When n=1, it is TN01; when n=2, it is TN02.
[0016] When n=1, it is TN03; when n=2, it is TN04.
[0017] When n=1, it is TN05; when n=2, it is TN06.
[0018] When n=1, it is TN07; when n=2, it is TN08.
[0019] TN09; TN010; TN11; TN12;
[0020] TN13;
[0021] When n=1, it is TN14; when n=2, it is TN15.
[0022] Preferably, the conductive glass substrate is fluorine-doped tin oxide or indium tin oxide, and its thickness is 1.5 to 2 mm.
[0023] Preferably, the chemical composition of the electron transport layer is one of tin dioxide, zinc oxide, tungsten oxide, titanium dioxide, methyl [6,6]-phenyl C71 butyrate, methyl [6,6]-phenyl C61 butyrate, and organic fullerene materials, and the thickness of the electron transport layer is 80-100 nm.
[0024] Preferably, the chemical composition of the perovskite light-absorbing layer is ABX3;
[0025] A includes CH6N + (MA + CH5N2 + (FA + ), Cs + One or more of the following;
[0026] B includes Ge 2+ Cu 2+ Mn 2+Pb 2+ and Sn 2+ One of them;
[0027] X includes Cl - ,Br - and I - One or two of them;
[0028] The thickness of the perovskite light-absorbing layer is 400–600 nm.
[0029] Preferably, the chemical composition of the hole transport layer includes one of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene, poly(3,4-ethylenedioxythiophene-polystyrene sulfonate), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], copper phthalocyanine, cuprous thiocyanate, poly(3-hexylthiophene), and nickel oxide, and the thickness of the hole transport layer is 80–120 nm.
[0030] Preferably, the metal electrode includes one of Au, Ag, Cl and Al, and the thickness of the metal electrode is 100-140 nm.
[0031] A method for fabricating perovskite solar cells based on interfacial chemical reactions includes the following steps:
[0032] S1 prepares an electron transport layer dispersion, coats the electron transport layer dispersion onto a conductive substrate, and performs a first annealing to form an electron transport layer;
[0033] The S11 electron transport layer dispersion is prepared by mixing the chemical components of the electron transport layer with a dispersion; the dispersion is one of deionized water, ethanol, methanol and butanol, and the mass fraction of the dispersion is 2-4 wt%.
[0034] The S12 coating method is spin coating, with a spin coating speed of 3000-4000 rpm / min and a spin coating time of 30-40 s.
[0035] The first annealing temperature for S13 is 150–180℃, and the first annealing time is 30–45 min.
[0036] S2 prepares a perovskite light-absorbing layer precursor solution, coats the perovskite light-absorbing layer precursor solution onto the surface of the above-mentioned electron transport layer, and performs a second annealing to form a perovskite light-absorbing layer.
[0037] The chemical composition of the perovskite light-absorbing layer is ABX3. The perovskite light-absorbing layer precursor solution includes an organic solvent containing BI2 and an organic solvent containing Al and CH6NCl (aminomethane hydrochloride).
[0038] The preparation method of the S21 perovskite light-absorbing layer precursor solution is to mix BI2 with organic solvent one to obtain an organic solvent containing BI2; and to mix Al and CH6NCl with organic solvent two to obtain an organic solvent containing Al and CH6NCl.
[0039] The organic solvent is a mixed solution of DMF and DMSO, with a volume ratio of DMF to DMSO of 9:1 to 1.5, and the concentration of BI2 is 1.4 to 1.6 mol / L.
[0040] Organic solvent two is one of isopropanol, ethanol, methanol, dichloromethane, chloroform, butanol, tetrahydrofuran, and acetone;
[0041] The total concentration of Al and CH6NCl was 0.6–0.8 mol / L, and the molar ratio of Al to CH6NCl was 3.8:1.2.
[0042] The S22 coating method is spin coating, with a rotation speed of 1500-2500 rpm / min and a time of 30-40 s. The spin coating is carried out in a glove box.
[0043] The second annealing process of S23 is as follows: an organic solution containing BI2 is coated onto the surface of the electron transport layer, and the first stage of the second annealing is performed. After the annealing is completed, an organic solution of Al and CH6NCl is coated onto the BI2 layer, and the second stage of the second annealing is performed to obtain the perovskite light-absorbing layer.
[0044] The first stage of annealing is carried out at a temperature of 70–90°C for 1–5 minutes in a glove box. The second stage of annealing is carried out at a temperature of 120–150°C for 12–15 minutes in air, as water vapor in the air helps the perovskite light-absorbing layer crystallize. The air humidity is 35–40%.
[0045] S3 prepares a perovskite modified layer dispersion, coats the perovskite modified layer dispersion onto the surface of the above perovskite light-absorbing layer, and performs a third annealing to form a perovskite modified layer.
[0046] The perovskite modified layer dispersion was prepared by mixing the interface modification molecules with an organic solvent, which was one of toluene, ethyl acetate and chlorobenzene, and the concentration of the interface modification molecules was 2 to 2.5 mmol / L.
[0047] The coating method was spin coating, with a spin speed of 5000 rpm / min and a spin coating time of 30 s. The third annealing temperature was 80-100℃, and the time was 5-10 min. The third annealing was carried out in a glove box.
[0048] S4 prepares a hole transport layer dispersion, and coats the hole transport layer dispersion onto the surface of the perovskite modified layer to form a hole transport layer.
[0049] The method for preparing the S41 hole transport layer dispersion includes mixing 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene, 4-tert-butylpyridine and lithium bis(trifluoromethanesulfonylimide) with organic solvent tetra.
[0050] The organic solvent is one or more of toluene, chlorobenzene, and xylene; the content of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene is 70-80 mg / ml, the content of 4-tert-butylpyridine is 20-30 mg / ml, and the content of lithium bis(trifluoromethanesulfonylimide) is 3.0-5.0 mg / ml.
[0051] The S42 coating method is spin coating, with a spin speed of 4000 rpm / min and a spin time of 30 s. Spin coating is carried out in a glove box.
[0052] S5 deposits the corresponding metal electrode onto the hole transport layer to form a metal electrode, thus obtaining a perovskite solar cell.
[0053] Vacuum evaporation vacuum degree is less than 1×10 -4 pa, the vacuum evaporation rate is
[0054] Preferably, the method for preparing the perovskite modified layer dispersion in step 3) includes the following steps:
[0055] Under inert gas protection, S31 feeds a core-containing chemical component and a dendron-containing chemical component in a molar ratio of 1:2 to 1:2.5, along with a catalyst palladium acetate, a ligand tri-tert-butylphosphine, a base sodium tert-butoxide, and an organic solvent toluene. The reaction is carried out at 80–100 °C for 24–48 h to obtain intermediate product one.
[0056] Under inert gas protection, intermediate product one and p-fluoronitrobenzene were fed in a molar ratio of 1:2 to 1:2.5, along with catalyst NaH and organic solvent N,N-dimethyl sulfoxide. After a pre-reaction of 1 h, p-fluoronitrobenzene was slowly added, and the reaction was carried out at 120 to 140 °C for 24 to 48 h to obtain intermediate product two.
[0057] S33 feeds intermediate product II and stannous chloride at a molar ratio of 1:10 to 1:20, and adds organic solvent ethanol. The reaction is carried out at a temperature of 80 to 100°C for 12 to 24 hours to obtain intermediate product III.
[0058] Under inert gas protection, the intermediate product S34 was dissolved in an appropriate amount of toluene, and triphosgene was slowly added dropwise under ice-water bath conditions. After the addition was completed, the temperature was raised to 80-120℃ and the reaction was carried out for 24-40 hours to obtain the interface-modified molecule.
[0059] S35 mixes the interface-modifying molecules with an organic solvent to obtain a perovskite-modified layer dispersion.
[0060] The beneficial effects of this invention are:
[0061] This invention provides an interface-modifying molecule as a raw material for a perovskite modification layer. The interface-modifying molecule reacts chemically with A-site ions in the light-absorbing layer of a perovskite solar cell, utilizing the strong reactivity of isocyanate groups and amine groups, to undergo the following reaction:
[0062]
[0063] By firmly and stably attaching the perovskite modification layer to the perovskite light-absorbing layer, the smoothness of the perovskite solar cell's light-absorbing layer interface is improved. Simultaneously, due to the hole transport performance of the triphenylamine structure and the p-type organic semiconductor characteristics and hydrophobicity of the aforementioned interface modification molecules, and the interaction between the C=O double bonds in the formed structure and the Pb in the perovskite structure... 2+ The coordination effect of the substance passivates the interface defects, improves the energy level matching between the light-absorbing layer and the hole transport layer, and enhances the hydrophobicity of the light-absorbing layer of the perovskite solar cell, thereby improving the efficiency and stability of the fabricated perovskite solar cell.
[0064] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0065] Figure 1 This is a schematic diagram of the structure of the perovskite solar cell of the present invention;
[0066] Figure 2 This is the 1H NMR spectrum of TN02 in Example 4 of the present invention;
[0067] Figure 3 This is the infrared absorption spectrum of TN02 in Embodiment 4 of the present invention;
[0068] Figure 4 This is a stability comparison diagram between Embodiment 2 and Comparative Example 1 of the present invention;
[0069] Figure 5 This is a performance comparison chart of Embodiment 2 of the present invention with Comparative Examples 1 and 2. Detailed Implementation
[0070] The present invention will be further described below with reference to embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should have the ordinary meaning understood by one of ordinary skill in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.
[0071] Example 1
[0072] This invention provides a perovskite solar cell based on interfacial chemical reactions, comprising a conductive glass substrate, an electron transport layer, a perovskite light-absorbing layer, a perovskite modification layer, a hole transport layer, and a metal electrode stacked thereon. The conductive glass substrate is fluorine-doped tin oxide, the electron transport layer is tin dioxide, the perovskite light-absorbing layer has the chemical composition CH5N2PbI3, the perovskite modification layer is TN02, and the hole transport layer has the chemical composition 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene, 4-tert-butylpyridine, and lithium bis(trifluoromethanesulfonyl)imide.
[0073] The above-mentioned method for fabricating perovskite solar cells includes the following steps:
[0074] S1 prepares an electron transport layer dispersion, coats the electron transport layer dispersion onto a conductive substrate, and performs a first annealing to form an electron transport layer.
[0075] S11 prepared an electron transport layer dispersion by mixing tin dioxide with methanol at a mass fraction of 2 wt%.
[0076] The S12 coating method is spin coating, with a spin coating speed of 3000 rpm / min and a spin coating time of 30 s.
[0077] The first annealing temperature of S13 is 150℃, and the first annealing time is 3 minutes. The dispersant is removed by the first annealing, forming a dense electron transport layer.
[0078] S2 prepares a perovskite light-absorbing layer precursor solution, coats the perovskite light-absorbing layer precursor solution onto the surface of the above-mentioned electron transport layer, and performs a second annealing to form a perovskite light-absorbing layer.
[0079] The chemical composition of the perovskite light-absorbing layer is CH5N2PbI3. The perovskite light-absorbing layer precursor solution includes an organic solvent containing PbI2 and an organic solvent containing CH5N2I (formamidinium hydroiodide) and CH6NCl (aminomethane hydrochloride).
[0080] The preparation method of the S21 perovskite light-absorbing layer precursor solution is to mix PbI2 with organic solvent one to obtain an organic solvent containing PbI2; wherein the organic solvent one is a mixed solution of DMF and DMSO, the volume ratio of DMF to DMSO is 9:1, and the concentration of PbI2 is 1.4 mol / L.
[0081] CH5N2I and CH6NCl were mixed with isopropanol to obtain an organic solvent containing CH5N2I and CH6NCl; the total concentration of CH5N2I and CH6NCl was 0.6 mol / L, and the molar ratio of CH5N2I to CH6NCl was 3.8:1.2.
[0082] The S22 coating method is spin coating, with a rotation speed of 1500 rpm / min and a time of 30 seconds, and the spin coating is carried out in the glove box.
[0083] The second annealing process of S23 is as follows: an organic solution containing PbI2 is coated onto the surface of the electron transport layer, and the first stage of the second annealing is performed. After the annealing is completed, an organic solution of CH5N2I and CH6NCl is coated onto the BI2 layer, and the second stage of the second annealing is performed to obtain the perovskite light-absorbing layer.
[0084] The first stage of annealing was carried out at a temperature of 70°C for 1 minute in a glove box. The second stage of annealing was carried out at a temperature of 120°C for 12 minutes in air, as water vapor in the air helps the perovskite light-absorbing layer crystallize. The air humidity was 35%.
[0085] S3 prepares a perovskite modified layer dispersion, coats the perovskite modified layer dispersion onto the surface of the above perovskite light-absorbing layer, and performs a third annealing to form a perovskite modified layer.
[0086] The perovskite modified layer dispersion was prepared by mixing TNO2 with toluene, with the concentration of TNO2 being 2 mmol / L.
[0087] The coating method was spin coating, with a spin speed of 5000 rpm / min and a spin coating time of 30 s. The third annealing temperature was 80℃ and the time was 5 min, and the third annealing was carried out in a glove box.
[0088] S4 prepares a hole transport layer dispersion, and coats the hole transport layer dispersion onto the surface of the perovskite modified layer to form a hole transport layer.
[0089] The method for preparing the S41 hole transport layer dispersion includes mixing 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene, 4-tert-butylpyridine and lithium bis(trifluoromethanesulfonylimide) with toluene;
[0090] The content of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene is 70 mg / ml, the content of 4-tert-butylpyridine is 20 mg / ml, and the content of lithium bis(trifluoromethanesulfonyl)imide is 3.0 mg / ml.
[0091] The S42 coating method is spin coating, with a spin speed of 4000 rpm / min and a spin time of 30 s. Spin coating is carried out in a glove box.
[0092] In step S5, Au electrodes are deposited onto the hole transport layer to form a metal electrode, resulting in a perovskite solar cell. The vacuum deposition vacuum level is below 1×10⁻⁶. -4 pa, the vacuum evaporation rate is
[0093] Example 2
[0094] This invention provides a perovskite solar cell based on interfacial chemical reactions, comprising a conductive glass substrate, an electron transport layer, a perovskite light-absorbing layer, a perovskite modification layer, a hole transport layer, and a metal electrode stacked thereon. The conductive glass substrate is fluorine-doped tin oxide, the electron transport layer is tin dioxide, the perovskite light-absorbing layer has the chemical composition CH5N2PbI3, the perovskite modification layer is TN02, and the hole transport layer has the chemical composition 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene, 4-tert-butylpyridine, and lithium bis(trifluoromethanesulfonyl)imide.
[0095] The above-mentioned method for fabricating perovskite solar cells includes the following steps:
[0096] S1 prepares an electron transport layer dispersion, coats the electron transport layer dispersion onto a conductive substrate, and performs a first annealing to form an electron transport layer.
[0097] S11 prepared an electron transport layer dispersion by mixing tin dioxide with methanol at a mass fraction of 3 wt%.
[0098] The S12 coating method is spin coating, with a spin coating speed of 4000 rpm / min and a spin coating time of 30 s.
[0099] The first annealing temperature of S13 is 150℃, and the first annealing time is 25 minutes. The dispersant is removed by the first annealing, forming a dense electron transport layer.
[0100] S2 prepares a perovskite light-absorbing layer precursor solution, coats the perovskite light-absorbing layer precursor solution onto the surface of the above-mentioned electron transport layer, and performs a second annealing to form a perovskite light-absorbing layer.
[0101] The chemical composition of the perovskite light-absorbing layer is CH5N2PbI3. The perovskite light-absorbing layer precursor solution includes an organic solvent containing PbI2 and an organic solvent containing CH5N2I (formamidinium hydroiodide) and CH6NCl (aminomethane hydrochloride).
[0102] The preparation method of the S21 perovskite light-absorbing layer precursor solution is to mix PbI2 with organic solvent one to obtain an organic solvent containing PbI2; wherein the organic solvent one is a mixed solution of DMF and DMSO, the volume ratio of DMF to DMSO is 9:1, and the concentration of PbI2 is 1.5 mol / L.
[0103] CH5N2I and CH6NCl were mixed with isopropanol to obtain an organic solvent containing CH5N2I and CH6NCl; the total concentration of CH5N2I and CH6NCl was 0.7 mol / L, and the molar ratio of CH5N2I to CH6NCl was 3.8:1.2.
[0104] The S22 coating method is spin coating, with a rotation speed of 2000 rpm / min and a time of 30 seconds, and the spin coating is carried out in a glove box.
[0105] The second annealing process of S23 is as follows: an organic solution containing PbI2 is coated onto the surface of the electron transport layer, and the first stage of the second annealing is performed. After the annealing is completed, an organic solution of CH5N2I and CH6NCl is coated onto the BI2 layer, and the second stage of the second annealing is performed to obtain the perovskite light-absorbing layer.
[0106] The first stage of annealing was carried out at a temperature of 90°C for 3 minutes in a glove box. The second stage of annealing was carried out at a temperature of 150°C for 13 minutes in air, as water vapor in the air helps the perovskite light-absorbing layer crystallize. The air humidity was 35%.
[0107] S3 prepares a perovskite modified layer dispersion, coats the perovskite modified layer dispersion onto the surface of the above perovskite light-absorbing layer, and performs a third annealing to form a perovskite modified layer.
[0108] The perovskite modified layer dispersion was prepared by mixing TNO2 with toluene, with a TNO2 concentration of 2.3 mmol / L.
[0109] The coating method was spin coating, with a spin speed of 5000 rpm / min and a spin coating time of 30 s. The third annealing temperature was 90℃ and the time was 8 min, and the third annealing was carried out in a glove box.
[0110] S4 prepares a hole transport layer dispersion, and coats the hole transport layer dispersion onto the surface of the perovskite modified layer to form a hole transport layer.
[0111] The method for preparing the S41 hole transport layer dispersion includes mixing 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene, 4-tert-butylpyridine and lithium bis(trifluoromethanesulfonylimide) with toluene;
[0112] The content of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene was 73 mg / ml, the content of 4-tert-butylpyridine was 26 mg / ml, and the content of lithium bis(trifluoromethanesulfonyl)imide was 4.5 mg / ml.
[0113] The S42 coating method is spin coating, with a spin speed of 4000 rpm / min and a spin time of 30 s. Spin coating is carried out in a glove box.
[0114] In step S5, Au electrodes are deposited onto the hole transport layer to form a metal electrode, resulting in a perovskite solar cell. The vacuum deposition vacuum level is below 1×10⁻⁶. -4 pa, the vacuum evaporation rate is
[0115] Example 3
[0116] This invention provides a perovskite solar cell based on interfacial chemical reactions, comprising a conductive glass substrate, an electron transport layer, a perovskite light-absorbing layer, a perovskite modification layer, a hole transport layer, and a metal electrode stacked thereon. The conductive glass substrate is fluorine-doped tin oxide, the electron transport layer is tin dioxide, the perovskite light-absorbing layer has the chemical composition CH5N2PbI3, the perovskite modification layer is TN02, and the hole transport layer has the chemical composition 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene, 4-tert-butylpyridine, and lithium bis(trifluoromethanesulfonyl)imide.
[0117] The above-mentioned method for fabricating perovskite solar cells includes the following steps:
[0118] S1 prepares an electron transport layer dispersion, coats the electron transport layer dispersion onto a conductive substrate, and performs a first annealing to form an electron transport layer;
[0119] S11 prepared an electron transport layer dispersion by mixing tin dioxide with 4 wt% methanol.
[0120] The S12 coating method is spin coating, with a spin coating speed of 4000 rpm / min and a spin coating time of 40 s.
[0121] The first annealing temperature of S13 is 180℃, and the first annealing time is 45 minutes. The dispersant is removed by the first annealing, forming a dense electron transport layer.
[0122] S2 prepares a perovskite light-absorbing layer precursor solution, coats the perovskite light-absorbing layer precursor solution onto the surface of the above-mentioned electron transport layer, and performs a second annealing to form a perovskite light-absorbing layer.
[0123] The chemical composition of the perovskite light-absorbing layer is CH5N2PbI3. The perovskite light-absorbing layer precursor solution includes an organic solvent containing PbI2 and an organic solvent containing CH5N2I (formamidinium hydroiodide) and CH6NCl (aminomethane hydrochloride).
[0124] The preparation method of the S21 perovskite light-absorbing layer precursor solution is to mix PbI2 with an organic solvent to obtain an organic solvent containing PbI2; wherein the organic solvent is a mixed solution of DMF and DMSO, the volume ratio of DMF to DMSO is 9:1.5, and the concentration of PbI2 is 1.6 mol / L.
[0125] CH5N2I and CH6NCl were mixed with ethanol to obtain an organic solvent containing CH5N2I and CH6NCl; the total concentration of CH5N2I and CH6NCl was 0.8 mol / L, and the molar ratio of CH5N2I to CH6NCl was 3.8:1.2.
[0126] The S22 coating method is spin coating, with a rotation speed of 2500 rpm / min and a time of 40 seconds, and the spin coating is carried out in the glove box.
[0127] The second annealing process of S23 is as follows: an organic solution containing PbI2 is coated onto the surface of the electron transport layer, and the first stage of the second annealing is performed. After the annealing is completed, an organic solution of CH5N2I and CH6NCl is coated onto the PbI2 layer, and the second stage of the second annealing is performed to obtain the perovskite light-absorbing layer.
[0128] The first stage of annealing was carried out at 90°C for 5 minutes in a glove box. The second stage of annealing was carried out at 150°C for 15 minutes in air, as water vapor in the air helps the perovskite light-absorbing layer crystallize. The air humidity was 40%.
[0129] S3 prepares a perovskite modified layer dispersion, coats the perovskite modified layer dispersion onto the surface of the above perovskite light-absorbing layer, and performs a third annealing to form a perovskite modified layer.
[0130] The perovskite modified layer dispersion was prepared by mixing TN02 with toluene, with the concentration of TN02 being 2.5 mmol / L.
[0131] The coating method was spin coating, with a spin speed of 5000 rpm / min and a spin coating time of 30 s. The third annealing temperature was 100℃ and the time was 10 min, and the third annealing was carried out in a glove box.
[0132] S4 prepares a hole transport layer dispersion, and coats the hole transport layer dispersion onto the surface of the perovskite modified layer to form a hole transport layer.
[0133] The method for preparing the S41 hole transport layer dispersion includes mixing 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene, 4-tert-butylpyridine and lithium bis(trifluoromethanesulfonylimide) with xylene;
[0134] The content of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene is 80 mg / ml, the content of 4-tert-butylpyridine is 25 mg / ml, and the content of lithium bis(trifluoromethanesulfonyl)imide is 5.0 mg / ml.
[0135] The S42 coating method is spin coating, with a spin speed of 4000 rpm / min and a spin time of 30 s. Spin coating is carried out in a glove box.
[0136] S5 involves vapor-depositing Ag electrodes onto the hole transport layer to form a metal electrode, resulting in a perovskite solar cell. The vacuum deposition vacuum level is below 1×10⁻⁶. -4 pa, the vacuum evaporation rate is
[0137] Example 4
[0138] The difference from Example 2 is that the perovskite modified layers are TN01, TN03, TN04, TN05, TN06, TN07, TN08, TN09, TN010, TN11, TN12, TN13, TN14, and TN15, respectively, while the rest are the same as in Example 2.
[0139] Example 5
[0140] Preparation of interface-modified molecules
[0141] Taking N,N'-di-p-isocyanophenyl-N,N'-di-p-tolylbenzidine (TN02) as an example
[0142] (1) Synthesis of N,N'-di-p-tolylbenzidine (intermediate product one)
[0143]
[0144] Under argon protection, 4,4'-diiodobiphenyl (8.12 g, 20 mmol), p-toluidine (4.71 g, 44 mmol), sodium tert-butoxide (9.61 g, 100 mmol), Pd₂(dba)₃ (0.92 g, 1 mmol), and tri-tert-butylphosphine (1.16 g, 4 mmol) were added to a 250 mL single-necked flask. A suitable amount of solvent was added, and the mixture was stirred and refluxed at 115 °C for 15 h. After the reaction was complete, extraction and drying yielded 4.78 g of a gray powder, with a yield of 87.5%.
[0145] (2) Synthesis of N,N'-di-p-nitrophenyl-N,N'-di-p-tolylbenzidine (intermediate product 2)
[0146]
[0147] Under argon protection, N,N'-di-p-tolylbenzidine (10.935 g, 30 mmol) was added to a 500 mL flask and dissolved in 180 mL of DMF. NaH (3.6 g, 90 mmol) was added, and the reaction was carried out at room temperature for 1 h. After the pre-reaction was complete, p-fluoronitrobenzene (8.7 g, 62 mmol) was slowly added, and the temperature was raised to 140 °C for 48 h. After the reaction was completed and cooled to room temperature, the reaction solution was poured into 100 mL of ice water. The precipitated yellow solid was filtered, and the filter cake was washed three times with 50 mL of water and dried under vacuum to obtain 14.7 g of N,N'-di-p-nitrophenyl-N,N'-di-p-tolylbenzidine solid, with a yield of 80.7%.
[0148] (3) Synthesis of N,N'-di-p-aminophenyl-N,N'-di-p-tolylbenzidine (intermediate product 3)
[0149]
[0150] Under argon protection, stannous chloride monohydrate (SnCl2·H2O, 11.28 g, 25 mmol), N,N'-di-p-nitrophenyl-N,N'-di-p-tolylbenzidine (3.03 g, 5 mmol), and 90 mL of ethanol were added to a 250 mL flask, and the mixture was refluxed for 16 h. Excess tin salt was removed with NaOH, and the crude product was obtained by column chromatography. Recrystallization from toluene yielded 1.08 g of pale yellow powder of N,N'-di-p-aminophenyl-N,N'-di-p-tolylbenzidine, with a yield of 39.5%.
[0151] (4) Synthesis of N,N'-di-p-isocyanophenyl-N,N'-di-p-tolylbenzidine (TN02)
[0152] Under argon protection, N,N'-di-p-aminophenyl-N,N'-di-p-tolylbenzidine (0.82 g, 1.5 mmol), triphosgene CO(COCl3)2 (0.30 g, 1.0 mmol), and 30 mL of anhydrous dichloroethane were added to a 50 mL flask, and the mixture was stirred at 100 °C for 8 h. After the reaction was complete, the mixture was cooled to room temperature, evaporated to dryness, and then dried under vacuum at room temperature to give 0.583 g of the green product N,N'-di-p-isocyanophenyl-N,N'-di-p-tolylbenzidine (TNO2), with a yield of 65%.
[0153] Comparative Example 1
[0154] The difference from Example 2 is that no perovskite modification layer was used.
[0155] Comparative Example 2
[0156] The difference from Example 2 is that the TNO2 molecule is replaced with C8H20BrN (octylammonium bromide).
[0157] Performance tests were conducted on the perovskite solar cells prepared in Example 2 and Comparative Example 1.
[0158] Figure 4 This is a comparison graph showing the stability of perovskite solar cells in Example 2 and Comparative Example 1. Figure 4 As can be seen, the modified device still maintains 80% efficiency after running at maximum power point for 6000 minutes, while the unmodified device only has 40% of the original efficiency, indicating that the stability of the modified device is significantly improved.
[0159] Performance tests were performed on the perovskite solar cells prepared in Example 2, Comparative Examples 1 and 2.
[0160] Figure 5 This is a performance comparison graph of the perovskite solar cells of Example 2 and Comparative Example 1. Figure 5 As can be seen, the short-circuit current Isc of the modified device decreased from 24.38 mA / cm². -2 Increased to 25.00 mA / cm -2 The open-circuit voltage Voc increased from 1.15V to 1.18V, the fill factor increased from 76% to 80%, and the device efficiency increased from 21.56% to 23.57%, achieving higher efficiency than devices obtained by ordinary coordination modification.
[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A perovskite solar cell based on interfacial chemical reactions, characterized in that: It includes a conductive glass substrate, an electron transport layer, a perovskite light-absorbing layer, a perovskite modification layer, a hole transport layer, and a metal electrode, which are stacked in sequence. The chemical composition of the perovskite light-absorbing layer is ABX3; A includes CH6N. + (MA + CH5N2 + (FA + One or more of the following: B includes Ge 2+ Cu 2+ Mn 2+ Pb 2+ and Sn 2+ One of them; X includes Cl - ,Br - and I - One or two of them; The structural formula of the interface modification molecules used in the perovskite modification layer is: Wherein, core is a core group with large conjugation, and dendron is a dendritic group with isocyanate substituents; core is , , , , , , , , One of them; R1 and R2 are one of straight-chain alkyl, branched alkyl, methoxy, and vinyl groups.
2. The perovskite solar cell based on interfacial chemical reaction according to claim 1, characterized in that: dendron for , One of them; wherein R3 is an isocyanate group, and R4 is one of a straight-chain alkyl group, a branched alkyl group, or a methoxy group.
3. The perovskite solar cell based on interfacial chemical reaction according to claim 1, characterized in that: The conductive glass substrate is fluorine-doped tin oxide or indium tin oxide, with a thickness of 1.5~2mm.
4. A perovskite solar cell based on interfacial chemical reaction according to claim 1, characterized in that: The electron transport layer is composed of one of the following: tin dioxide, zinc oxide, tungsten oxide, titanium dioxide, methyl [6,6]-phenyl C71 butyrate, methyl [6,6]-phenyl C61 butyrate, and organic fullerene materials. The thickness of the electron transport layer is 80~100 nm.
5. A perovskite solar cell based on interfacial chemical reaction according to claim 1, characterized in that: The thickness of the perovskite light-absorbing layer is 400~600nm.
6. A perovskite solar cell based on interfacial chemical reaction according to claim 1, characterized in that: The chemical composition of the hole transport layer includes one of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene, poly(3,4-ethylenedioxythiophene-polystyrene sulfonate), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], copper phthalocyanine, cuprous thiocyanate, poly(3-hexylthiophene), and nickel oxide. The thickness of the hole transport layer is 80~120 nm.
7. A perovskite solar cell based on interfacial chemical reaction according to claim 1, characterized in that: The metal electrode includes one of Au, Ag, Cl and Al, and the thickness of the metal electrode is 100~140 nm.
8. A method for preparing a perovskite solar cell based on interfacial chemical reactions according to any one of claims 1-7, characterized in that, Includes the following steps: S1 prepares an electron transport layer dispersion, coats the electron transport layer dispersion onto a conductive substrate, and performs a first annealing to form an electron transport layer; S2 prepares a perovskite light-absorbing layer precursor solution, coats the perovskite light-absorbing layer precursor solution onto the surface of the above-mentioned electron transport layer, and performs a second annealing to form a perovskite light-absorbing layer. S3 prepares a perovskite modified layer dispersion, coats the perovskite modified layer dispersion onto the surface of the above perovskite light-absorbing layer, and performs a third annealing to form a perovskite modified layer. S4 prepares a hole transport layer dispersion, and coats the hole transport layer dispersion onto the surface of the perovskite modified layer to form a hole transport layer. S5 deposits the corresponding metal electrode onto the hole transport layer to form a metal electrode, thus obtaining a perovskite solar cell.
9. The method for preparing a perovskite solar cell based on interfacial chemical reaction according to claim 8, characterized in that: The preparation method of the perovskite modified layer dispersion in S3 includes the following steps: Under inert gas protection, S31 is prepared by feeding a chemical component containing core and a chemical component containing dendron in a molar ratio of 1:2 to 1:2.5, along with a catalyst palladium acetate, a ligand tri-tert-butylphosphine, a base sodium tert-butoxide, and an organic solvent toluene. The reaction is carried out at 80–100 °C for 24–48 h to obtain intermediate product one. Under inert gas protection, intermediate product one and p-fluoronitrobenzene were fed in a molar ratio of 1:2 to 1:2.5, along with catalyst NaH and organic solvent N,N-dimethyl sulfoxide. After a pre-reaction of 1 h, p-fluoronitrobenzene was slowly added, and the reaction was carried out at 120 to 140 °C for 24 to 48 h to obtain intermediate product two. S33 feeds intermediate product II and stannous chloride at a molar ratio of 1:10 to 1:20, and adds organic solvent ethanol. The reaction is carried out at a temperature of 80 to 100°C for 12 to 24 hours to obtain intermediate product III. Under inert gas protection, the intermediate product S34 was dissolved in an appropriate amount of toluene, and triphosgene was slowly added dropwise under ice-water bath conditions. After the addition was completed, the temperature was raised to 80~120℃ and the reaction was carried out for 24~40h to obtain the interface-modified molecule. S35 mixes the interface-modifying molecules with an organic solvent to obtain a perovskite-modified layer dispersion.
Citation Information
Patent Citations
Stable and efficient perovskite solar cell and preparation method thereof
CN112133833A
Novel polyurethane and application thereof
CN113817123A